PENGGUNAAN MEDIA POP-UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN BUDAYA DAERAH DI KELAS V SD INPRES PERUMNAS 1 - Rido, Debrina Eunike; Taty R. Koroh; Martha Khristina Kota (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve students’ learning outcomes on the topic of regional cultural diversity through the use of Pop-Up Book media in Grade V of SD Inpres Perumnas 1 Kota Kupang. The problem identified in this study was the low learning outcomes of students caused by teacher-centered instruction and limited use of innovative learning media. The objective of this study was to enhance students’ learning outcomes through the implementation of Pop-Up Book media. This research used Classroom Action Research (CAR) consisting of two cycles, each including planning, action, observation, and reflection. The subjects were 20 fifth-grade students. Data were collected through learning outcome tests and observation sheets of teacher and student activities. The results showed that the implementation of Pop-Up Book media significantly improved students’ learning outcomes. The average score increased from 63.25 with 45% mastery in Cycle I to 80.75 with 90% mastery in Cycle II. In addition, teacher and student activities also improved from the “fair” category in Cycle I to the “very good” and “good” categories in Cycle II. These findings indicate that Pop-Up Book media is effective in improving students’ understanding, learning motivation, and learning outcomes in cultural diversity material.